Gender Differences in Job Satisfaction and Work-Life Balance Among Chinese Physicians in Tertiary Public Hospitals - Liu, Dan; Wu, Yinuo; Jiang, Feng; Wang, Mingxiao; Liu, Yuanli; Tang, Yi-Lang (Frontiers in Public Health, 2021)
Background: Gender has been associated with job-related experience, including job satisfaction and work-life balance. This study aimed to identify gender differences in job satisfaction and work-life balance among Chinese physicians in a large, nationally representative sample. Methods: A national cross-sectional survey was conducted between March 18 and 31, 2019, using an anonymous online questionnaire. The questionnaire included the short-form MSQ (Chinese version) and a work-life balance item. The demographic and job-related factors were also collected. Findings: In total, 22,128 physicians (9,378 males and 12,750 females) from 144 tertiary public hospitals completed the survey. The overall MSQ score (job satisfaction) was 70.31 ± 12.67, and it was 69.89 ± 13.24 in males, and 70.63 ± 12.22 in females, respectively (p < 0.001). Only 931 (4.21%) physicians were very satisfied with WLB (421 males, 510 females), and 2,534 (11.45%) were rated as satisfied. Age, education, monthly income, working hours, specialty, and professional titles were significantly associated with job satisfaction; while number of children, specialty, professional titles, monthly income, age, working hours were significantly associated with WLB. No significant gender differences were observed in job satisfaction or WLB after controlling confounding factors (both p > 0.05). Interpretation: While many demographic and work-related factors are significantly associated with job satisfaction and WLB, we found no significant gender differences, which is different from many other studies. To improve Chinese physicians' job satisfaction and work-life balance, interventions should be focused on certain specialties and on other modifiable factors, such as income, working hours.